Efisiensi Penggunaan Reagen NaOH Terhadap Pengujian Kadar Protein pada Alat Buchi KjelFlex K-360 - Soesilowati (UIN Sunan Kalijaga Yogyakarta, 2022)
The purpose of this study was to determine the efficiency of the use of NaOH reagents with different volumes at the distillation stage of the Kjeldahl method for testing protein levels using the Buchi KjelFlex K-360. The protein content test was carried out using the Kjeldahl method with variations in the volume of NaOH at the distillation stage of 20 mL, 30 mL, 40 mL, 50 mL, 60 mL, 70 mL, 80 mL, and 90 mL. The results showed that the protein content obtained from each use of the NaOH reagent at the distillation stage with different volumes, respectively, was 6.66%; 6.81%; 6.88%; 6.79%; 6.68%; 6.81%; 6.70%; and 6.73%. Based on these results, at different volumes, the protein content obtained shows a value that is not much different, so the use of NaOH reagent in small amounts can increase the efficiency of the use of NaOH reagent in the distillation stage of the Kjeldahl method. It is hoped that this can be used as an alternative in an effort to reduce the use of operational costs and reduce waste accumulation resulting from the analysis process.